High‐Dimensional Image Analysis using Histocytometry. Issue 6 (24th June 2021) - Munoz‐Erazo, Luis; Schmidt, Alfonso J.; Price, Kylie M.
Abstract: Histocytometry is a technique for processing multiparameter microscopy images using computational approaches to identify and quantify cellular phenotypes. It allows for spatial analyses of cellular phenotypes in relation to each other and within defined spatial regions. The benefit of this technique over manual annotation and characterization of cells is a high degree of automation/throughput, significantly decreased user bias, and increased reproducibility. Recently, an increase in freely available software amenable to or deliberately designed for histocytometry has resulted in these complex analyses being available to a broader base of users who have amassed multi‐component microscopic imaging data. This article provides an overview of a histocytometry pipeline, focusing on the strategic planning and software requirements to allow readers to perform cell segmentation, phenotyping, and spatial analyses to advance their research outputs. © 2021 Wiley Periodicals LLC.